COVID-19: Digital Transformation as a Force for Resilience - Oliveira, Selma; Castro Leite, Yasmim (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
This study highlighted digital transformation, the transformation of accounting in the context of the COVID 19 pandemic, in light of the experiences of Brazilian multinational corporations from different sectors. Specifically, this study highlighted the relevance of digital transformation, through dynamic capabilities, for accounting / multinational corporations to become resilient in the context of the COVID 19 pandemic. Thus, using a scalar-type questionnaire, a survey was carried out with accounting professionals (accountants, controllers, analysts, coordinators, supervisors, etc.) of said corporations. The findings signaled that resilience was enhanced through dynamic capabilities, with emphasis on adaptability. This study is original and has implications for the practice of accounting, signaling the priorities of capabilities to achieve resilience in times of crisis or turmoil. This study represents a guide for managers in the accounting area, showing which skills need to focus their efforts. Furthermore, this research advances the body of knowledge for accounting theory.